Capital Market Integration in ASEAN Countries: Special Investigation of Indonesian Towards the Big Four - Suryanta, Barli (The Asian Journal of Technology Management (AJTM), 2011)
ASEAN already proposed financial integration through capital market integration based on ASEAN Economics Community (AEC) 2020 treaty in order to aim comprehensive ASEAN economic integration. The objective of this study is to occur the capacity of Indonesian in terms of integrating its capital market towards the big four i.e., Singaporean, Malaysian, Philippines, and Thailand.Â  Vector Auto-regression (VAR) analysis is utilized to investigate Indonesian market returns co-movement and dynamic link with ASEAN 4. The conclusion of this study, there is neither co-movement nor strong dynamic link between Indonesian capital market with those of Singaporean, Malaysian, Philippines, and Thailand. Keywords: ASEAN Capital market integration, Indonesian Capital Market, ASEAN 4 Capital Market, VAR Framework.